Penyusunan Alat Bantu Ajar untuk anak TK dan SD Mengenai Literasi Stasiun Kereta “Navi Station” - Weningtyas, Widyarini; Widyanesti Liritantri (Mitra Teras: Jurnal Terapan Pengabdian Masyarakat, 2023)
Abstract The current rapid and extensive development of rail-based transportation systems, both operationally and in terms of their infrastructure, raises the question of the readiness and awareness of the public, especially among the younger generation, to keep pace with these advancements. The swift evolution of technology, coupled with the increasing complexity of rail networks and the growing number of stations, often leaves train users, especially newcomers, bewildered. This confusion stems from the fact that the procedures for boarding, as well as the ethical culture and safety practices associated with each type of train, vary and have their own specific regulations. Therefore, there is a need for educational efforts in the fields of station literacy, social and ethical culture, and safety.The objectives of this initiative are as follows 1) Introducing various types of trains, including their corporate logos and mascots; 2) Enhancing knowledge about station literacy; 3) Promoting an ethical culture within train stations; 4) Disseminating safety messages at train stations and level crossings. The outcomes of this community-based empowerment program include 1) Increasing the knowledge of our partners, encompassing the readiness of children as the future generation to use trains operating in Indonesia; 2) Fostering polite and rule-abiding ethical behavior in trains and train stations; 3) Cultivating safety-conscious behavior among children and teachers in trains, train stations, and level crossings. Educational aids for this endeavor will employ play-based media designed in accordance with the learning outcomes for Early Childhood Education and Elementary School, encompassing three aspects: Religion and Morality, Self-Identity, and Fundamentals of Literacy and STEAM (Science, Technology, Engineering, Arts, and Mathematics). Abstrak Perkembangan dan pembangunan moda transportasi berbasis rel saat ini berlangsung sangat cepat dan masif baik dari aspek operasional maupun sistemnya. Lalu yang menjadi pertanyaan bagaimana kesiapan (readiness) dan kesadaran (awareness) masyarakat dalam mengikuti perkembangan tersebut terlebih lagi generasi anak-anak. Pesatnya perkembangan teknologi, diiringi dengan semakin kompleksnya jalur jaringan kereta dan bertambahnya jumlah stasiun sering kali membuat pengguna kereta apalagi pengguna baru kebingungan. Hal ini disebabkan oleh informasi cara naik serta budaya beretika dan keselamatan untuk masing-masing jenis kereta akan mempunyai perbedaan dan peraturannya masing-masing. Oleh karena itu, dibutuhkan edukasi di bidang pendidikan mengenai literasi stasiun, bidang sosial budaya (budaya beretika) dan bidang keselamatan. Tujuan dari kegiatan ini yaitu 1) Memperkenalkan berbagai jenis kereta dari logo perusahaan dan maskot; 2) Meningkatkan pengetahuan literasi stasiun; 3) Meningkatkan pengetahuan budaya beretika di stasiun; 4) Menyampaikan pesan keselamatan di stasiun kereta dan perlintasan sebidang. Luaran dari pemberdayaan berbasis masyarakat ini yakni meningkatkan pengetahuan mitra meliputi 1) Kesiapan anak-anak sebagai generasi mendatang agar dapat naik kereta yang beroperasi di Indonesia; 2) Terciptanya perilaku beretika yang santun dan sesuai aturan yang diberlakukan di kereta dan stasiun kereta ; 3) Terciptanya perilaku berkeselamatan di kalangan anak-anak dan juga guru di kereta, stasiun kereta, dan perlintasan sebidang. Media alat bantu ajar yang akan dipakai menggunakan media berbasis bermain yang akan didesain sesuai dengan capaian Pembelajaran untuk Pendidikan Anak Usia Dini dan SD yang terdiri dari tiga aspek, yaitu Agama dan Akhlak, Jati diri, dan Dasar-Dasar Literasi dan STEAM.